Analysis of Business Development In Laptopin.Id Store Through The Triple Layered Business Model Canvas Approach - Istiqomah, Chairunnisa; Hendrayati, Heny; Sultan, Mokh Adib (Entrepreneurship Faculty, Universitas Garut, 2023)
Digitalization forces people to be able to utilize technology in their daily activities. Laptops are a supporting tool for doing work to learning. The used laptop business is booming with prices that are much cheaper than new laptops. With intense competition, a business model is needed so that the business can continue to survive and develop. The purpose of this research is to project the Laptop in business model which will produce the best strategy for decision-making considerations in the context of developing an ongoing business using the Triple Layered Business Model Canvas. The method used in this research is a descriptive method with a case study approach. The steps taken are (1) SWOT Analysis Formulation, (2) Triple Layered Business Model Canvas Strategy Formulation, and (3) PMIA Method. Where this research finds that businesses are in a growth and build position through an integrative strategy by working on the B2B market, in mapping the business model 3 aspects can help Laptop in to create business value, namely (1) economic aspects, by creating consumer forums to create loyal consumers (2) environmental aspects, processing electronic waste through third parties and (3) social aspects, providing opportunities for persons with disabilities to become part of the shop employees. Decision-making on the TLBMC Laptop in elements using the PMIA (Plus Minus Implication Analysis) method gives a total PMIA score sequentially from largest to smallest, namely the economic layer +39, the environmental layer +33, and the social layer +29. These results indicate that the current decision-making in Laptop in business development is appropriate and feasible to continue.